Probing SU(2) symmetry breaking in the nucleon sea - Arash, Firooz [UNESP]; Tomio, Lauro [UNESP] (Elsevier, 1997)
Investigation of invariant cross-sections for production of K*- and K*0, in the fragmentation region of the proton, in p - p and γ - p reactions, gives a direct and unambiguous probe to the symmetry breaking of the nucleon sea. Based on existing data, we clearly found a large asymmetry of the sea. Our result is in excellent agreement with NA51 measurement, signaling lack of any nuclear effect. The measurement can be carried out in a single experimental set up. The ratio K*-/K*0 is equivalent to ū/d̄, with easy access to the x-dependence of the asymmetry. The observed asymmetry from available experimental data is used to improve the valon-recombination model. © 1997 Elsevier Science B.V.
Keywords: Experimental tests; Flavor symmetries; Meson production; Quark models